Microhabitat selection and daily movements of two rodents (Necromys lasiurus and Oryzomys scotti) in Brazilian Cerrado, as revealed by a spool-and-line device - Vieira, E. M.; Iob, G.; Briani, D. C.; Palma, ART (Elsevier B.V., 2005)
Studies on patterns of habitat use by mammals are necessary for understanding the mechanisms involved in their distribution and abundance. In this study, we used the spool-and-line method to investigate habitat utilization by two sigmodontine rodents from Brazilian Cerrado, Necromys lasiurus and Oryzomys scotti. We conducted the study in a Cerrado area in central Brazil (15 degrees 56'S and e 47 degrees 56'W) where the animals were caught in an area of 7.68 ha of Cerrado sensu stricto. Captured individuals were marked, equipped with a spool-and-Line device, and released at the same capture point. The next day we followed the thread to record their daily movements and find their nests. To investigate microhabitat selection we compared habitat characteristics along traits of each studied species with general habitat characteristics of the study area. Although the mean 24-h distance was greater for N. lasiurus (mean +/- SE: 41.9 +/- 42.2 m, N=3) than for O. scotti (28.7 +/- 14.2 m, N=6) this difference was not significant (Mann-Whitney test, U=26, P>0.6). We detected significant differences among observed microhabitats variables of both species and available microhabitat characteristics as determined by discriminant analysis (Wilks's lambda F=3.001; df=14, 116; P<0.001). Both species were associated to microhabitat characteristics whose values differed markedly from the overall available habitat. Along the first canonical discriminant function of the DFA both them were associated with greater grass height than the mean height available and along the second axis N. lasiurus selected areas with higher fruit availability and more shelters than those selected by 0. scotti. For stronger inferences regarding differential patterns of habitat utilization by Cerrado rodents we suggest the simultaneous use of both spool-and-line and standard trapping methods. (c) 2005 Deutsche Geseltschaft fur Saugetierkunde. Published by Elsevier GmbH. ALL rights reserved.
Keywords: Oryzomys scotti; Necromys lasiurus; habitat utilization; rodents